TORASEMIDE IN PREVENTION OF MITRAL REGURGITATION AND CHRONIC HEART FAILURE WORSENING IN POSTINFARCTION PERIOD - A. A. Abdullaev; I. B. Ibragimova; U. A. Islamova; R. M. Gafurova; N. N. Baytemirova (Российский кардиологический журнал, 2018)
In the review, the results of scientific research provided, conducted with aim to study influence of ischemic mitral regurgitation (IMR) on the development and progressionof chronic heart failure (CHF). The opportunities considered, of torasemide implementation in prevention of the raise of mitral regurgitation grade, development of desadaptive remodelling of the heart, decrease of its electrical instability that presents itself with various cardiac rhythm disorders, and of prevention ofdevelopment and progression of the CHF. Benefits of torasemide over furosemideare revealed in management of congestive CHF at the background of IMR inpostinfarction patients.